A Protocol for Direct Stereospecific Amination of Primary, Secondary, and Tertiary Alkylboronic Esters - Edelstein, Emma K.; Grote, Andrea C.; Palkowitz, Maximilian D.; Morken, James P. (Synlett, 2018)
The direct, stereospecific amination of alkylboronic and borinic esters can be conducted by treatment of the organoboron compound with methoxyamine and potassium tert-butoxide. In addition to being stereospecific, this process also enables the direct amination of tertiary boronic esters in an efficient fashion.
Keywords: organoboron; asymmetric synthesis; amination; chiral amines; stereochemistry